Power Electronics: Historical Notes, Recent Advances And Contemporary Challenges - Tan, Don (Eletrônica de Potência, 2020)
This paper attempts to summarize 10 major contemporary challenges for power electronics and system technology (PEAS technology). Historical background is first reviewed together with most recent technological advances. Recent advances are then discussed in detail. A recent breakthrough in megawatt system design and design verification is highlighted. We then articulate the challenges that PEAS technology is facing contemporarily. They are: Powering smart buildings, smart factories, and smart infrastructure, Renewable energy integration and structured microgrids, EV drives and vehicle power systems, Ultra-fast and ultra-efficient chargers, Appliances - “White goods,” Server and data center power systems’ Wireless power transfer, Powering IoT and wireless sensor networks, Storage and “power dump,” and ATGC (All things grid connected), system integration, and dynamic control. These 10 areas present technical barriers for us to overcome and anticipated progress will help define the future of power electronics and its impact to the power and energy industry at large.